12(2x-1)=9(2x+1)+9

Simple and best practice solution for 12(2x-1)=9(2x+1)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(2x-1)=9(2x+1)+9 equation:


Simplifying
12(2x + -1) = 9(2x + 1) + 9

Reorder the terms:
12(-1 + 2x) = 9(2x + 1) + 9
(-1 * 12 + 2x * 12) = 9(2x + 1) + 9
(-12 + 24x) = 9(2x + 1) + 9

Reorder the terms:
-12 + 24x = 9(1 + 2x) + 9
-12 + 24x = (1 * 9 + 2x * 9) + 9
-12 + 24x = (9 + 18x) + 9

Reorder the terms:
-12 + 24x = 9 + 9 + 18x

Combine like terms: 9 + 9 = 18
-12 + 24x = 18 + 18x

Solving
-12 + 24x = 18 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
-12 + 24x + -18x = 18 + 18x + -18x

Combine like terms: 24x + -18x = 6x
-12 + 6x = 18 + 18x + -18x

Combine like terms: 18x + -18x = 0
-12 + 6x = 18 + 0
-12 + 6x = 18

Add '12' to each side of the equation.
-12 + 12 + 6x = 18 + 12

Combine like terms: -12 + 12 = 0
0 + 6x = 18 + 12
6x = 18 + 12

Combine like terms: 18 + 12 = 30
6x = 30

Divide each side by '6'.
x = 5

Simplifying
x = 5

See similar equations:

| q(2+3q)-q(5q-7)= | | 0.15x+0.05(4-x)=0.10(12) | | .25(.9x)=nx | | 4(s+3)-1=3x-5 | | 21/4x-1/2 | | -3(1-9z)-(-11z-11)= | | 3(-7-2x)+6(3x-7)=-51 | | 2x-6x+3x= | | 34=-2(2p+5)+5(1-7p) | | X=1.75+1.75X | | 3(t+7)-4=17 | | -4n-4(n-1)=12 | | 5=1+n-2 | | 5x^3+14x^2-3x=0 | | -(1-6x)-5=12 | | (a^4*-ac)+(c^3*d^2)= | | 5/7x15 | | 15x+25y=1400 | | c/5-c-1/10=9/10 | | 5X+7-2x=-11 | | 2y-10x=70 | | 17=3t+5 | | 5x-3y+2x+y= | | 6=3s-3 | | 3.12-d+2.1=1.910 | | (8+7i)-(-2+3i)= | | c-2.2+7.35=9.2 | | 2x+81=99 | | B-4.14=2.13-1.14 | | (X^2)-(0.5x)-(0.6)=0 | | -6+n=-2n | | C-2.2+7.35=9.3 |

Equations solver categories